A case report on recurrent subphrenic abscess with pulmonary tuberculosis - Gayathre, S. P.; Kumar, R. Niranjan; Silambuselvi, K. (International Surgery Journal, 2023)
Subphrenic abscess though a common presentation itself encountered in surgical practice due to various cause, a tubercular subphrenic abscess in the absence of coexisting tuberculous abdomen presenting as a complication of pulmonary tuberculosis is extremely rare. Only a very few cases have been reported as an extrapulmonary manifestation of tuberculosis so far. We report a case of isolated sub-diaphragmatic abscess which responded well with anti-tuberculous therapy despite all other interventions.